Pakistan: Impacts of COVID-19 on Production, Poverty & Food Systems - Moeen, Muhammad Saad; Haider, Zeeshan; Shikoh, Sania Haider; Rizwan, Noormah; Ejaz, Amna; Davies, Stephen; Rana, Abdul Wajid (2021)
By Muhammad Saad Moeen, Zeeshan Haider, Sania Haider Shikoh, Noormah Rizwan, Amna Ejaz, Stephen Davies and Abdul Wajid Rana This presentation has been developed under the Pakistan Agriculture Capacity Enhancement (PACE) program funded by the United States Agency for International Development (USAID) Updated: December 30, 2020